Immediate and short‐term outcomes after percutaneous atrial septal defect closure using the new nit‐occlud ASD‐R device. Issue 3 (27th February 2014) - Peirone, Alejandro; Contreras, Alejandro; Ferrero, Adolfo; da Costa, Rodrigo Nieckel; Pedra, Simone Fontes; Pedra, Carlos A.C.
<x xml:space="preserve">Abstract</x> Objectives To evaluate the feasibility, safety, and efficacy of implantation of the new Nit Occlud ASD‐R® (NOASD‐R) device for percutaneous closure of ostium secundum atrial septal defects (ASD‐OS). Background Device catheter implantation has become the method of choice for most patients with ASD‐OS. No single device has proven to be ideal for this type of procedure. The NOASD‐R has a distinct design that may help to overcome limitations of other devices. Methods A prospective, single arm, observational study including all consecutive patients receiving the NOASD‐R device for ASD‐OS closure between October 2011 and September 2013 was performed. Patient selection, device design, deployment technique, complications, and procedural outcomes were evaluated. Results Seventy‐four patients underwent attempted transcatheter ASD‐OS closure using the NOASD‐R device. Implantation of the occluder was successful in 73 patients (98.6%). The majority of patients were female (79.5%) with a median age of 17.2 years (range: 2–74). A 2‐D transthoracic color‐Doppler echocardiogram (TTE) obtained at the 3 or 6 month follow‐up visit showed complete occlusion of the ASD‐OS in 72/73 patients (98.6%). At a mean follow‐up interval of 11.4 ± 6.8 months there have been no episodes of late device embolization, cardiac perforation or erosion, endocarditis, thromboembolism, wire fracture, embolic neurologic events, or death. Conclusions We report the first worldwide clinical experience using the NOASD‐R device for ASD‐OS closure. The procedure was feasible, with a high rate of successful implantations, and safe. High ASD‐OS closure rates and no complications were encountered during short‐term follow‐up. © 2014 Wiley Periodicals, Inc.